P241 The feasibility and validity of objective cough monitoring in children using an adult cough detection system. (12th November 2015) - Deblej Elghamoudi, D; Sumner, H; McGuiness, K; Smith, J; Murray, CS
Abstract : Background: In young children the evaluation of symptoms is almost wholly reliant upon parental reporting. Cough is extremely common in childhood and a tool to objectively measure cough frequency would be clinically beneficial. To date paediatric cough monitoring systems have relied on manual cough counting which is time consuming and costly. The VitaloJAK™ (Vitalograph, UK) is a custom built 24 hr semi-automated cough monitoring device that has been used successfully to quantify cough in adults. Using the VitaloJAK™ we tested the feasibility of 24 hr cough recordings in children and tested existing compression software for cough quantification. Methods: Children (age 2–14 years) with acute or chronic cough were asked to wear VitaloJAK™ cough monitor for a maximum of 24 h. Feedback about the device was obtained from the child/carer were appropriate. All recordings were manually counted and also processed through the compression software. Results: 40 children (21 male; mean age 8 yrs) wore the monitor for a median of 22.25 h (0.38 – 24 hrs). Children who wore the monitor as out-patients with chronic cough generally wore the monitor for longer (median 23.07 hrs) than those who were in-patients with acute symptoms (median 12.59 hrs; p = 0.06). Twenty-nine children (73%) wore the monitor for >12 h and 22 for >22 hrs including during the night. Eighteen (45%) children reported the monitor was heavy/bulky and eleven (28%) said at times it restricted some normal daily tasks (bending/stooping/using the toilet). Neither length of time the monitor was worn for, nor complaints about the size or restricting nature of the monitor, were age dependent. No serious adverse events were reported. One recording was excluded due to technical problems. Recordings demonstrated wide variability in frequency from 2 to 2712 coughs per recording (median 72). Following compression a median of 98.5% (85.7–100) of coughs were retained. Conclusions: VitaloJAK™ semi-automated cough monitor can be used in children to accurately measure cough frequency. As with many medical interventions, it was not tolerated by all children for long periods, however the majority of children were able to wear it for >12 h.